حتقيق النصوص لكتاب االعتكاف يف خمطوطة شرح منهاج الطالبن - Rahmi Amir; Syarifuddin Syarifuddin; Muhammad Saleh; M. Dahlan M. (Al-Qalam, 2021)
This paper is entitled: "Manuscript of I'tikaf on the Book of Syarah Minhaj Ath-Thalibin." Is a scientific work that discuss  Manuscript of I'tikaf on the Book of Syarah Minhaj Ath-Thalibin  ( philological analysis)  with two problem analyzes : How  condition of the text The Manuscript I'tikaf in the Book of Syarah Minhaj Ath- Thalibin? How critique of the text The Manuscript I'tikaf in the Book of Syarah Minhaj Ath- Thalibin? To finishing problems, researchers use scientific methods that include collection methods in the form of text criticism analysis theory and literature methods. On the stage of data collection using the library method then at the stage of data presentation using the narrative descriptive method and the critical method of the text. The text of the I'tikaf Manuscript in the Kitab Syarah Minhaj Ath-Thalibin belongs to Ashaf Zein He work as a teacher in one of the schools in Mandar inherited from his father Kiai Ahmad Bin Muh. Zein on located in Bonde village, Campalagian District, Polewali Mandar Regency. In general, the text of the manuscript is still good, but does not have some writing errors and the loss of some letters, words and sentences.